UTILIZATION OF SOCIAL MEDIA IN PROVIDING PUBLIC INFORMATION BY THE DEPARTMENT OF EDUCATION AND CULTURE OF JOMBANG REGENCY, INDONESIA - Maheswari Jelita Adristi (Jurnal Sosiologi Dialektika Sosial, 2026)
This study examines the use of social media by the Public Relations of the Jombang Regency Education and Culture Office in disseminating public information. The research problem stems from the tendency of government public relations communication to remain one-way, despite utilizing digital media such as Instagram and the official website. This study uses a descriptive qualitative method with data collection techniques such as observation of Instagram and website content over the past six months, digital archive documentation, and in-depth interviews with public relations staff. The analytical tools used are Max Weber's legitimacy theory and Jürgen Habermas's public sphere theory. Data analysis was carried out through reduction, presentation, and drawing conclusions using triangulation of sources and techniques. The results show that Instagram is actively used as a medium for publishing activities and announcements, while the website functions as the institution's official archive. However, public relations communication practices are still dominated by a one-way pattern with a low level of public interaction. From the perspective of Weber's legitimacy theory, digital media functions as a means of maintaining bureaucratic legitimacy. Meanwhile, based on Habermas's public sphere theory, digital media has not fully functioned as a dialogue space between the state and society. This study emphasizes that the digital transformation of government public relations requires a change in communication paradigm to be more participatory and responsive.